PEMODELAN KEJADIAN BANJIR DAERAH ALIRAN SUNGAI CILIWUNG HULU DENGAN MENGGUNAKAN DATA RADAR - Putiamini, Sepanie; Kusratmoko, Eko; Syamsudin, Fadli (UI Scholars Hub, 2017)
. This study reports the applicability of hydrological modeling, HEC-HMS, integrated with Geographic Information Systems (GIS) to examine the rainfall - runoff relationship with a case study of Upper Ciliwung watershed. Spatial rainfall data derived from radar data used in the process of simulating rainfall - runoff and the results are compared with simulation results using the observed rainfall data. Analysis of the rainfall-runoff simulation was conducted based on spatial approach by comparing the differences and similarities between sub catchments. The simulations carried out for the flood events in 2002, 2007 and 2013. The results of the simulation of rainfall - runoff using C-Dopller weather rainfall radar data shows the sub-watershed of Ciliwung (Tugu) produced discharge with the highest volume in January - February 2002 and 2007, and also 16 - 17 January 2013, i.e. 117 mm, 124 mm and 46 mm, respectively. Physical characteristics of the watershed such as slope, land use, and soil type, are the factors that determine the high discharge value. The results of validation using RMSE and Nash produces small deviation value of the observation data. It shows that the use of weather radar data is reliable in the rainfall-runoff simulation in the Upper Ciliwung watershed